Hervormde hermeneutiese perspektiewe op Skrifverstaan en die Nuwe Testament - Geyser, Piet A. (HTS teologiese studies, 2017)
This article reflects on hermeneutics in the widest sense of the concept and not on the detailed technicalities from philosophical and other perspectives. Hermeneutics will be taken to refer to the whole act and process of understanding. It is done with special reference to how the understanding of Scripture and specifically the New Testament of theologians of the Netherdutch Reformed Church over the past seven decades, is reflected in the work in the HTS Theological Studies journal. It is clear that their approach to the understanding and concretisation of the message of the New Testament was one of greatest respect for Scripture. The basic tenet throughout was that the Word of God was to be found in the Bible. There was no assumption that Bible and Word of God were identified on one and the same level. Taking the Bible as literature seriously implied that the best scientific methods had to be found and implemented in this search for the meaning of the Word of God for the Church’s message and practice in the world.